Effect of GA3 on Enhancement of In-vivo Seed Germination in Givotia rottleriformis (Euphorbiaceae) -an Endangered Forest Tree - Rambabu, M.; Ujjwala, D.; Ugandhar, T.; Praveen, M.; Upender, M.; Swamy, N. Rama (Indian Forester, 2005)
Givotia rottleriformis Griff. (Vern: Tel-Tella Poniki), the White catamaran deciduous tree, is traditionally used in the toy industry. Due to regular cutting and over exploitation, this species has become endangered. Propagation of this species is mainly through seed and the natural regeneration of the species through seed is very poor. In order to enhance the seed germination percentage, the seeds were treated with different concentrations and durations of GA3. The results of germination evaluation after 36 hrs of sowing revealed the beneficial effects of GA3. (3%) over the rest with 90 per cent germination against 5 per cent in control. It was observed that the GA3. treated seeds showed the enhancement in germination and breakage of seed dormancy in the species. Thus the present methodology can be used for in-situ conservation of the species.